Do international migration and remittances reduce poverty in developing countries? - Adams jr., Richard H. (2005)
Analyses a new data set on international migration, remittances, inequality, and poverty from 71 developing countries. Determines that both international migration and remittances significantly reduce the level, depth and severity of poverty in the developing world.